Translation and validation of the Nepean Dyspepsia Index for functional dyspepsia in China - Tian, Xiao-Ping; Li, Ying; Liang, Fan-Rong; Sun, Guo-Jie; Yan, Jie; Chang, Xiao-Rong; Ma, Ting-Ting; Yu, Shu-Yuan; Yang, Xu-Guang (World journal of gastroenterology : WJG, 2009)
AIM： To assess the reliability and validity of the translated version of Nepean Dyspepsia Index （NDI） in Chinese patients with documented functional dyspepsia （FO）. METHODS： The translation process included forward translation, back translation, pretest and cross-cultural adaptation. Reliability and validity of the translated version were examined by asking 300 subjects to complete the Chinese version of the NDI. The mean age of subjects was 39.24 years and 68.7% of the subjects were women. Internal consistency analysis with Cronbach＇s α was performed to test the reliability. Correlation analysis was used to assess the content validity. Factor analysis and structural equation models were used to assess the construct validity. RESULTS： The Cronbach＇s α coefficients ranged 0.833-0.960, well above the acceptable level of 0.70. Correlation analysis showed that each item had a strong correlation with the corresponding domain, but a weak correlation with other domains. Confirmatory factor analysis indicated that the comparative fit index was 0.94, higher than the acceptable level of 0.90.CONCLUSION： The Chinese version of the NDI is a reliable and valid scale for measuring health-related quality of life and disease severity in Chinese patients with FD.